Water-selective adsorption sites on detonation nanodiamonds. (November 2018) - Piña-Salazar, Elda-Zoraida; Kukobat, Radovan; Futamura, Ryusuke; Hayashi, Takuya; Toshio, Sakai; Ōsawa, Eiji; Kaneko, Katsumi
Abstract: Nanodiamond particles form aggregates having porosity in the range of micropores to mesopores with an average pore diameter of 4.5 nm. The measured porosity depends on the removal of pre-occupied water and gases from the nanodiamond aggregates, which is sensitive to thermal treatments. We heated hydrogel nanodiamonds at 423–623 K in vacuo in order to understand the relationship between water adsorptivity and pore structure evaluated from nitrogen and argon adsorption isotherms at 77 K and 87 K, respectively. Temperature-programmed evolved gas analysis showed the evolution of water and CO2 on heating nanodiamonds in vacuo up to 700 K. The surface functional groups of nanodiamonds were not affected by the thermal treatments, as shown by FTIR and XPS analyses. However, the water adsorptivity was enhanced by heating at 623 K due to the removal of the pore blocking effect originated from water molecules selectively adsorbed. Water molecules adsorbed on these selective sites should cause the intensive hygroscopic property of nanodiamonds. Graphical abstract: Image 1